Anti-money laundering and countering financing of terrorism legislation in Vietnam: Criminalization, Practice and Challenges - Thai, Ha Van (Essays of Faculty of Law University of Pécs, Yearbook of [year], 2023)
This paper aims to examine the effectiveness and suitability of the Vietnamese anti-money laundering (AML) and countering financing terrorism (CFT) regime. This paper has three parts. The first part of the paper will provide an overview of the Law on Anti-money laundering 2012 (the Law on AML) and the criminalization of money laundering offences in the Criminal Code 2015, amended in 2017. The second part of the paper seeks to examine the practice and challenges of the Vietnamese AML/CFT framework in terms of the (i) implementation of preventive measures adopted by the reporting institutions in order to preclude and identify money laundering cases; (ii) use of reporting and combating identifiable or suspected money laundering transactions to the relevant authorities; and (iii) domestic and international cooperation in AML. The third part of the paper will provide recommendations as referencing for other jurisdictions.